A variant in the LRRFIP1 gene is associated with adiposity and inflammation1. (16th March 2013) - Plourde, Melanie; Vohl, Marie‐Claude; Bellis, Claire; Carless, Melanie; Dyer, Thomas; Dolley, Guillaume; Marette, André; Després, Jean‐Pierre; Bouchard, Claude; Blangero, John; Pérusse, Louis
Abstract: Inflammation is an important factor linking abdominal obesity with insulin resistance and related cardiometabolic risk. A genome‐wide association study of adiposity‐related traits performed in the Quebec Family Study (QFS) revealed that a single‐nucleotide polymorphism (SNP) in the LRRFIP1 gene (rs11680012) was associated with abdominal adiposity ( P = 4.6 × 10 –6 ). Objective: The objective of this study was to assess the relationship between polymorphisms in LRRFIP1 gene and adiposity (BMI, fat mass (FM), waist circumference (WC), and computed tomography‐derived areas of total, subcutaneous and visceral abdominal adipose tissue) and markers of inflammation (C‐reactive protein (CRP) and interleukin‐6 (IL‐6)). Design and Methods: Using Sequenom, 16 tag SNPs in the LRRFIP1 gene, capturing 78% of the genetic variation, were genotyped in 926 participants of the QFS. Results: Eight SNPs (rs7575941, rs3769053, rs11689421, rs3820808, rs11680012, rs3806505, rs6739130, and rs11686141) showed evidence of association with at least two adiposity phenotypes and plasma levels of one marker of inflammation. The strongest evidence of association was observed with rs11680012, which explained 1.8–3.4% of the variance in areas of abdominal adiposity and 2.0% of the variation in CRP levels. Carriers of the rare allele of rs11680012 had ∼30% more abdominal adiposity ( P values between 2.7 × 10 –4 and 3.8 × 10 –6 ) and 75% higher CRP levels ( P = 1.6 × 10 –4 ) than the common allele in age and sex adjusted data. Rs11680012 is a G/C SNP converting an arginine into a threonine and this amino acid substitution may potentially alter exonic splicing. Conclusion: This gene may therefore represent a potential interesting target to investigate in further functional studies on adiposity and inflammation.